The neurophysiological Behavioral Perspective Model of consumer choice and its contribution to the intentional behaviorist research programme - Foxall, Gordon R. (Frontiers in Human Neuroscience, 2023)
Cognitive explanations raise epistemological problems not faced by accounts confined to observable variables. Many explanatory components of cognitive models are unobservable: beliefs, attitudes and intentions, for instance, must be made empirically available to the researcher in the form of measures of observable behaviour from which the latent variables are inferred. The explanatory variables are abstract and theoretical and rely, if they are to enter investigations and explanations, on reasoned agreement on how they can be captured by proxy variables derived from what people say and how they behave. Psychometrics must be founded upon a firm, intersubjective agreement among researchers and users of research on the relationship of behavioural measures to the intentional constructs to which they point and the latent variables they seek to operationalise. Only if these considerations are adequately addressed can we arrive at consistent interpretations of the data. This problem provides the substance of the intentional behaviourist research programme (Foxall, 2020) which seeks to provide a rationale for cognitive explanation. Within this programme, two versions of the Behavioural Perspective Model (BPM), an extensional portrayal of socioeconomic behaviour and a corresponding intentional approach, address the task of identifying where intentional explanation becomes necessary and the form it should take. This paper explores a third version, based on neurophysiological substrates of consumer choice as a contributor to this task.The nature of 'value' is closely related to the rationale for a neurophysiological model of consumer choice. The variables involved are operationally specified and measured with high intersubjective agreement. The intentional model (BPM-I), depicting consumer action in terms of mental processes like perception, deliberation and choice, extends the purview of the BPM to new situations and areas of explanation.